Present Situation of Field Training for the Students of Accounting in Saudi Universities: A Field Study on Female Students of the Accounting Department - Princess Nora University - Mhasen Ali Khalil Alhaj (University of Science and Technology, Yemen, 2017)
This study aimed to explore the present situation of field training for the students of the accounting education in Saudi Universities, so as to raise its level and make the best use of it to gain practical experience and professional skills in accounting and other relevant field skills. To achieve this, a field study was conducted on trainee students of the Accounting Department - Princess Nourah University. To collect data for the study, a questionnaire consisting of two parts was used and distributed to groups of female students who were selected through the stratified random method. The sample represented students who were expected to graduate from the department, and who were registered in the Field Training Program. The sample involved students from different three academic levels, and various training days. The results showed statistically significant differences at (α =0.05) in the type of training for building accounting knowledge and skills of the students in the accounting department. This is attributed to the different training institutions. The results also revealed that writing graduation research simultaneously with the training program, whose allotted time is inadequate, would reduce the chance of gaining the desired experiences of field training. It was also clear that discontinuous training would hinder the students from getting the appropriate training opportunities, and that conducting training during the summer semester seemed sufficient and appropriate. Keywords: Accounting education, Field training.